Federalism as an institutional device for peace in Somalia: prospects and challenges - Harun, Ibrahim (Department of Commercial Law, 2022)
Since the turn of the 20th century, there has been intensified use of federalism as a tool for conflict resolution. Scholars are divided, however, about the potential of federalism to manage conflict. Some argue that it can accommodate the aspirations of both national and regional actors. Others see it as a road to conflict or state disintegration. The debate over the pros and cons of federalism is undecidable as both sides make reasonable theoretical claims and can point to some evidence in support of their propositions. Hence, the lesson drawn from divergent views on federalism is that there is no single federal formula for peace in divided societies. Instead, the degree to which federal institutions can contribute to preserving peace depends on how these institutions respond to the characteristics of the societies they govern. The findings of this study are that Somalia's Provisional Constitution makes provision for a number of significant institutional features of federalism that, if correctly embraced, could enhance peace in Somalia. However, most of these provisions are defective. Some need follow up legislation, while others need to be agreed upon by both the federal government and the federal member states. This thesis further reveals that Somali societies are inherently federal. For instance, practices such as negotiation and reconciliation, decentralised decision-making, and transparent dispute resolution form part of the governance system in the traditional Somali society. If properly adapted and utilised, these features of the Somali traditional governance system can help to strengthen the federal political system in Somalia. The major argument of this dissertation is hence that in view of the peculiarities of the Somalia state, the federal values inherent in the Somali traditional governance system should be included in a new federal constitution. Only a federal system built on such traditional values will be conducive to peace and stability in Somalia and help stem the tide of secession currently threatening to tear the federation apart.